Fast and Slow Subpolar Ocean Responses to the North Atlantic Oscillation: Thermal and Dynamical Changes. Issue 24 (17th December 2022) - Khatri, Hemant; Williams, Richard G.; Woollings, Tim; Smith, Doug M.
Abstract: Climate model hindcasts are analyzed to reveal the impacts of the North Atlantic Oscillation (NAO) on the North Atlantic subpolar ocean, which exhibits variability on seasonal to decadal timescales. The ocean response to a single winter NAO event is separated into fast and slow responses. The fast response persists over winter–spring seasons, during which wind stress and heat flux anomalies associated with the NAO rapidly modify ocean temperatures via changes in Ekman transport and ocean‐atmosphere heat exchanges. The slow response persists for 3–4 years, during which overturning and gyre circulations redistribute opposing‐signed surface temperature anomalies created by the NAO. This redistribution modifies east‐west temperature contrasts altering the meridional heat transport associated with gyres and changing the strength of the overturning circulation. Hence, the fast and slow responses lead to opposing‐signed subpolar temperature anomalies in time from the competing effects of local forcing and horizontal heat convergence. Plain Language Summary: The North Atlantic Oscillation (NAO) index is one of the most common metrics to characterize atmospheric regimes in the northern hemisphere, revealing how different patterns of atmospheric winds and air‐sea fluxes over Europe and North America affect the ocean state. In the present research, coupled climate model simulations are utilized to study the impacts of particular atmospheric events on the subpolar North Atlantic Ocean. Using NAO indices during the winter season, sets of multiple simulations having similar types of atmospheric events are created to carry out a composite analysis. The analyses reveal that the impact of atmospheric events on the oceans can last up to 4–5 years (or even longer in some cases). The fast response is controlled by the effect of the local winds and air‐sea heat fluxes, while the slow response is related to the role of the meridional overturning circulation and ocean gyres in transporting heat anomalies from the subtropics to the subpolar ocean. The combination of these fast and slow responses leads to the sign reversal of the subpolar surface temperature anomalies in time. Key Points: Subpolar ocean changes due to the North Atlantic Oscillation (NAO) are separated into competing fast, seasonal and slow, inter‐annual responses Fast response is related to the anomalous Ekman transport and air‐sea heat exchange associated with the NAO Slow response is due to the redistribution of subtropical temperature anomalies via overturning and gyre circulations